The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.18502/ijph.v48i11.3521
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidative and Anti-Inflammatory Activity of Kenya Grade AA Green Coffee Bean Extracts

Abstract: Background: Kenya AA green coffee bean extracts were tested for natural ingredients used for anti-oxidative and anti-inflammatory purposes in cosmetic products Methods: Anti-oxidative activities were measured by total polyphenol, 1,1-diphenyl-2-picrylhydrazyl (DPPH), and the 2,2′-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays. Anti-inflammatory activities were evaluated via nitric oxide (NO) assays, and through quantification of inducible nitric oxide synthase (iNOS), and cycloox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
1
3
0
2
Order By: Relevance
“…As expected, the in vitro antioxidant activity was found to be 4 times higher in the CGB sample than in the CSS, due to the higher polyphenol content, while the antityrosinase property is somewhat better in the CSS extract. The total polyphenol content is in line with that of other aqueous extracts obtained from CGB (169.00 ± 3.06 mg GA eq/g DW) [ 38 ] or hydroalcoholic extract from CGB (8.82 ± 0.12% w / w , gallic acid) [ 11 ]. Some discrepancies may be due, in addition to the extraction method, to the variety of coffee, the place of harvest, the storage conditions, and, of course, the fact that we compared defective CGB with commercial ones.…”
Section: Resultssupporting
confidence: 74%
“…As expected, the in vitro antioxidant activity was found to be 4 times higher in the CGB sample than in the CSS, due to the higher polyphenol content, while the antityrosinase property is somewhat better in the CSS extract. The total polyphenol content is in line with that of other aqueous extracts obtained from CGB (169.00 ± 3.06 mg GA eq/g DW) [ 38 ] or hydroalcoholic extract from CGB (8.82 ± 0.12% w / w , gallic acid) [ 11 ]. Some discrepancies may be due, in addition to the extraction method, to the variety of coffee, the place of harvest, the storage conditions, and, of course, the fact that we compared defective CGB with commercial ones.…”
Section: Resultssupporting
confidence: 74%
“…We found that the extraction yield was 2.38%. This extraction yield was lower that the previous studies (21,(28)(29)(30) because we performed a preextraction process using relatively nonpolar solvents to obtain an enriched extract with fewer nonpolar constituents. Additionally, the difference in the type of coffee bean and the extraction method (solvent, duration, temperature, solvent-sample ratios) might also affected the extraction yield.…”
Section: Extracts and Microparticles Yieldmentioning
confidence: 76%
“…The other plant-based products reported previously, the microencapsulation yield of vanilla extract, peanut sprout extract, red grape juice were reported 94.4, 89.01, and 39.00%, respectively (14)(15)(16) . Also, the utilization of WPC in GCB extract microencapsulation to the other material using maltodextrin (40-84%) (28)(29)(30)(31) and arabic gum (60%) (32) . This indicated that the type of wall material affected microencapsulation yield.…”
Section: Extracts and Microparticles Yieldmentioning
confidence: 99%
“…[142][143][144]) but also from vegetables (e.g., green lettuce (Lactuca sativa L.) [145], cabbage (Brassica spp.) [146,147]), and from other foodstuff, such as olive oil [148], cinnamon [149], edible mushrooms [150], fruits [151][152][153], fruit juices [154,155], or coffee [156][157][158]. From these studies, the ones addressing signalling pathways involved in the anti-inflammatory response highlight the downregulation of the same main molecular targets observed above for intestinal epithelium, i.e., NF-kB, iNOS, COX2, IL-1β, and IL-6, highlighting the specificity of natural molecules for these cellular biomarkers of inflammation.…”
Section: The Role Of Macrophages In Oxidative Stress and Inflammation...mentioning
confidence: 99%